[Cocoa Pods, Trinidad, B.W.I.] - (:unkn) unknown (Stephens Ltd., Trinidad, 2009)
A picture of cocoa pods on a branch. The pod contains the cacao beans that are fermented, roasted, and processed to extract cocoa powder and chocolate. Affixed to the back of the postcard is a Cuban 1 centavo stamp.
Colour: Coloured; Style: Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cacao--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Theobroma--Trinidad and Tobago; 1909